2018
DOI: 10.1007/s11259-017-9709-6
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen induces apoptotic neutrophil efferocytosis in horses

Abstract: Macrophages and neutrophils are important cellular components in the process of acute inflammation and its subsequent resolution, and evidence increasingly suggests that they play important functions during the resolution of chronic, adaptive inflammatory processes. Exacerbated neutrophil activity can be harmful to surrounding tissues; this is important in a range of diseases, including allergic asthma and chronic obstructive pulmonary disease in humans, and equine asthma (also known as recurrent airway obstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
1
12
1
Order By: Relevance
“…Our group has previously demonstrated in vitro that TX exerts its effect via a mechanism that is independent of its interaction with oestrogen receptors (ER) (Olave, Morales, et al, 2018). It has been shown that TX exerts many off‐target effects, and ultimately, it is possible that as a whole, these off‐target effects mediate the therapeutic effect of the drug (Mandlekar & Kong, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously demonstrated in vitro that TX exerts its effect via a mechanism that is independent of its interaction with oestrogen receptors (ER) (Olave, Morales, et al, 2018). It has been shown that TX exerts many off‐target effects, and ultimately, it is possible that as a whole, these off‐target effects mediate the therapeutic effect of the drug (Mandlekar & Kong, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…TX also dampens chemotactic index and respiratory burst production in equine peripheral blood neutrophils [ 16 ]; and this study shows that TX inhibits the chemokinetic effects of IL-8 in equine neutrophils. Furthermore, recent results show that incubation of neutrophils with 5 μm of tamoxifen induces their efferocytosis by macrophages [ 27 ]. All of the above could partially explain the anti-inflammatory effect of TX in horses with airway inflammation described by our group [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The few clinical studies that have looked into the potential use of TAM for equine airway inflammation have been based on a single dosage (approximately 0,25 mg/kg) extrapolated from human medicine, with conflicting results regarding clinical efficacy based on that single empirical dose [15,16]. However, there is robust pre-clinical information on modulation of inflammation, which warrants the pharmacokinetic and safety data presented here [17][18][19][20][21]. Oral TAM absorption was similar to findings in other species, since plasma concentration of TAM was maximum 3 h after oral administration, comparably to reports in humans and mice, where maximum concentration is also reached between 4 and 9 h postadministration [1].…”
Section: Discussionmentioning
confidence: 93%